Antifouling potential and microbial characterization of an electrochemical anaerobic membrane bioreactor utilizing membrane cathode and iron anode. (August 2021) - Zhao, Kai; Su, Fan; Gu, Kanghui; Qi, Jing; Liu, Ruiping; Hu, Chengzhi
Graphical abstract: Highlights: An electrochemical AnMBR coupled membrane cathode and iron anode was designed. A more porous and hydrophilic cake layer was formed in the eAnMBR. Fouling on membrane cathode was mitigated by electrical repulsion and gas scouring. Microbial community and methanogenic pathway were enriched in the eAnMBR. Abstract: Serious membrane fouling limits the application of anaerobic membrane bioreactors (AnMBRs) in sewage treatment. Herein, a novel electrochemical AnMBR (eAnMBR) was established by integrating electrocoagulation and a conductive membrane into an AnMBR. Compared with the traditional AnMBR, TP average removal rate increased by 24.97% and the membrane service cycle extended by 109.68% in the eAnMBR. Low extracellular polymeric substance concentration and large floc size were found in the mixed liquid of the eAnMBR due to the combined effect of coagulation and electric field, which induced a porous and hydrophilic cake layer, resulting in excellent water permeation capabilities. Additionally, the conductive membrane cathode effectively suppressed membrane fouling by the electrostatic repulsion and gas scouring. In the eAnMBR, the presence of an electric field and iron ions enriched the diversity of the microbial community, which may improve the adaptation of biochemical systems to environmental changes.